Leishmania spp Epitopes in Humans Naturally Resistant to the Disease: Working Toward a Synthetic Vaccine - Flórez, Magda Melissa; Rodríguez, Rocío; Cabrera, José Antonio; Robledo, Sara M.; Delgado, Gabriela (Frontiers in Cellular and Infection Microbiology, 2021)
Vaccines are one of the most effective strategies to fight infectious diseases. Reverse vaccinology strategies provide tools to perform in silico screening and a rational selection of potential candidates on a large scale before reaching in vitro and in vivo evaluations. Leishmania infection in humans produces clinical symptoms in some individuals, while another part of the population is naturally resistant (asymptomatic course) to the disease, and therefore their immune response controls parasite replication. By the identification of epitopes directly in humans, especially in those resistant to the disease, the probabilities of designing an effective vaccine are higher. The aim of this work was the identification of Leishmania epitopes in resistant humans. To achieve that, 11 peptide sequences (from Leishmania antigenic proteins) were selected using epitope prediction tools, and then, peripheral blood mononuclear cells (PBMCs) were isolated from human volunteers who were previously divided into four clinical groups: susceptible, resistant, exposed and not exposed to the parasite. The induction of inflammatory cytokines and lymphoproliferation was assessed using monocyte-derived dendritic cells (moDCs) as antigen-presenting cells (APCs). The response was evaluated after exposing volunteers’ cells to each peptide. As a result, we learned that STI41 and STI46 peptides induced IL-8 and IL-12 in moDCs and lymphoproliferation and low levels of IL-10 in lymphocytes differentially in resistant volunteers, similar behavior to that observed in those individuals to L. panamensis lysate antigens. We conclude that, in silico analysis allowed for the identification of natural Leishmania epitopes in humans, and also STI41 and STI46 peptides could be epitopes that lead to a cellular immune response directed at parasite control.